Effect Of Marketing Mix And Market Orientation On The Marketing Performance Of Pia Japanan Cake Business - Oktora, Yekie Senja; Sudarmiatin; Hermawan, Agus (CV. AFDIFAL MAJU BERKAH, 2022)
Performance Marketing is an important aspect in every company in order to maintain and maintain the company's survival and business development. Situation and condition current economic produce both products and services. This marketing performance is a concept to measure market performance of products, such as high market share and high marketing profitability, which are used as a reflection of the success of its business in the competitive business world. It is difficult for traders to understand market orientation, besides that, the completeness of the product is also an obstacle for traders in increasing marketing performance, the lack of effectiveness of distribution channels is also a factor inhibiting the marketing performance of traders, so the government needs to provide some kind of education and training for traders who are included in these MSMEs. The problem in this study is how the influence of the promotion mix and market orientation on marketing performance of Micro, Small and Medium Enterprises of Pia Japanan Cake Business The independent variables in this study are Marketing mix and market orientation and the dependent variable is marketing performance. The analysis model used is multiple linear regression analysis. The number of samples in this study were 184 respondents. The sampling technique uses a census. Based on the results of the study, it can be concluded that there is a significant influence of Marketing mix and market orientation variables on the marketing performance of MSMEs Pia Japanan Cake Business Marketing mix variables, market orientation and marketing performance have a strong relationship with the contribution of Marketing mix and market orientation to marketing performance which is also quite high that is equal to 82,2%, while the remaining 17.8% is determined by other factors outside the model.